PENERAPAN KOMUNIKASI NONVERBAL YANG DILAKUKAN PETUGAS KESEHATAN TERHADAP PASIEN COVID-19 DI RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SUBROTO - Andhika Bimo Prasojo (2021)
Health communication plays a very important role because the world is being shocked by the Covid-19 virus pandemic which can be transmitted from individual to individual. Health communication plays a role in steps to prevent and overcome the Covid-19 virus. The high death rate due to Covid-19 has made health workers on duty at the Gatot Subroto Army Central Hospital (RSPAD) to use PPE (Personal Protection Equipment) when at the hospital location, especially when interacting with Covid-19 patients. The large number of PPE components used by health workers makes it difficult to carry out nonverbal communication between health workers and patients. This study aims to determine how a nonverbal communication symbol can affect the patient's health condition as well as to study and find out the meaning created from the results of the ongoing communication between health workers and Covid-19 patients. The method used is a qualitative method with phenomenology on 5 health workers who are in charge of caring for Covid-19 patients. The results showed that the nonverbal communication carried out to newly admitted patients was usually in the form of a smile, a happy facial expression made the patient feel a little calmer and the patient responded by showing calmness after health workers made nonverbal communication.